Mathematics Learning Which Include with Character Values (Based on Findings at Guangxi Normal University and UNNES) - Suyitno, Hardi; Rochmad, Rochmad; Sugiharti, Endang; Suyitno, Amin; Yuanbing, Guo (KnE Social Sciences, 2019)
Character values need to be given to students from elementary school to university. These character values can be integrated into the learning process for all ﬁelds of study, including Mathematics. The problem: How do you teach a mathematics teacher or lecturer in the Mathematics Education Study Program to integrate character values in the learning process? This study involved partner lecturer, namely Prof. Guo Yuanbing from Guangxi Normal University. As a result, tips were obtained if a lecturer wanted to integrate character values in the learning process. The tips: (1) Lecturers provide exemplary attitudes, speaks, and actions that reﬂect noble character. (2) Lecturers provide information to students about the character values developed by the university. (3) Lecturers insert the character values on mathematical tasks. (4) Lecturers are strongly advised to evaluate the growth of character values in students. Suggestion: Universities should provide regulations on the need for lecturers to evaluate the emergence of student character values. Keywords: Character Value, Mathematics Learning, partner lecturer